2020
DOI: 10.1111/1365-2745.13347
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits that moderate tropical tree recruitment during post‐windstorm secondary succession

Abstract: 1. Understanding how functional traits moderate species' demographic responses along environmental gradients is a core pursuit in ecology, often to predict how | 1323

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 79 publications
(94 reference statements)
1
21
1
Order By: Relevance
“…It has been suggested and observed that increases in light due to canopy defoliation would promote colonization and growth of early-successional species (Myster and Walker 1997, Comita et al 2009, Hogan et al 2018, Lai et al 2020. We can support these findings post-Hurricane Maria where we saw increases in the dominance and percentage of early-successional species across all three elevations, individually, and in the forest as a whole (Appendix S1: Table S1).…”
Section: Forest Recovery: Alpha Diversitysupporting
confidence: 83%
See 1 more Smart Citation
“…It has been suggested and observed that increases in light due to canopy defoliation would promote colonization and growth of early-successional species (Myster and Walker 1997, Comita et al 2009, Hogan et al 2018, Lai et al 2020. We can support these findings post-Hurricane Maria where we saw increases in the dominance and percentage of early-successional species across all three elevations, individually, and in the forest as a whole (Appendix S1: Table S1).…”
Section: Forest Recovery: Alpha Diversitysupporting
confidence: 83%
“…2018, Lai et al. 2020). We can support these findings post‐Hurricane Maria where we saw increases in the dominance and percentage of early‐successional species across all three elevations, individually, and in the forest as a whole (Appendix : Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…To have a realistic initial neighbourhood composition, we used a joint species distribution model published from the same study site (Lai et al 2020) to predict the recruitment of each focal species in a given plot under 100% canopy openness and other environmental variables (i.e. leaf litter depth, soil nitrogen, phosphorous, potassium, and forest type) at their averages in the first census since wind disturbance.…”
Section: Methodsmentioning
confidence: 99%
“…We specifically compared ‘low’, ‘median’, and ‘high’ initial recruitment scenarios, which correspond to the 5th, 50th, and 95th percentiles of predicted recruitments. Because the Lai et al (2020) model also predicts that recruitment of other non-focal species would constitute roughly half (50.9%) of the total recruitment across species in a plot, we replaced these non-focal recruits with our focal recruits by doubling the predicted focal recruitments to obtain the focal species’ initial abundances; this resulted in 16, 26, and 46 initial stems for the ‘low’, ‘median’, and ‘high’ initial recruitment scenarios, respectively (Table S2). We assumed all recruits begin at 1-cm DBH and then used parameters inferred from both the ‘direct-interaction-only’ model (Equation 5) and the ‘HOI-inclusive’ model (Equation 6) to simulate individual diameter growth of focal species under the three recruitment scenarios at daily timesteps over two years—the time taken for canopy closure in our study site (Yee et al 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation